Effect of binding of ionised calcium on the in vitro nucleation of cholesterol and calcium bilirubinate in human gall bladder bile. Issue 11 (November 1986) - Gallinger, S; Harvey, P R; Petrunka, C N; Strasberg, S M
Abstract : Biliary calcium may be a nucleating agent in cholesterol cholelithiasis. A study was designed to determine the effect of binding of ionised calcium on in vitro nucleation time. Ultracentrifuged and microscopically clear gall bladder bile from cholesterol gall stone patients was divided into two aliquots. One aliquot served as control and ionised calcium was bound in the second aliquot by addition of EDTA. Nucleation time was observed for the two groups. Addition of EDTA had no effect on lipid composition of the biles. EDTA bound all ionised calcium. Calcium bilirubinate precipitated from all controls on day 1 but was absent in all samples with EDTA. Addition of EDTA had no effect on cholesterol crystal nucleation time; nucleation time was rapid in both the controls and samples with EDTA. Ionised calcium is essential for calcium bilirubinate precipitation but is not responsible for the rapid nucleation time of bile from cholesterol gall stone patients.